Temporal dynamics of nutrient uptake by neighbouring plant species: evidence from intercropping - Zhang, Wei-Ping; Liu, Guang-Cai; Sun, Jian-Hao; Fornara, Dario; Zhang, Li-Zhen; Zhang, Fang-Fang; Li, Long (Functional ecology, 2017)
Summary The productivity of species‐diverse plant assemblages strongly depends on the temporal dynamics of nutrient uptake by competing neighbouring plants. Our understanding, however, of how rates of nitrogen (N), phosphorous (P) and potassium (K) uptake might change through time between neighbouring plant species under field conditions is still very limited. Here, we specifically measure the temporal trajectories of N, P and K uptake by staple food plants such as wheat (Triticum aestivum L.), barley (Hordeum vulgare L.) and maize (Zea mays L.) when growing either in monocultures or in intercropping systems. We ask how (i) plant species combinations, (ii) N fertilization and (iii) film mulching might affect key indexes of N, P and K uptake over time. We fit logistic models to characterize the nutrient uptake trajectories. Maximum cumulative N, P and K uptake (kg ha−1) by wheat and barley were significantly greater in wheat–maize or barley–maize intercropping systems than in wheat or barley monocultures. Cumulative nutrient uptake by intercropped maize (either with wheat or with barley) was reduced by interspecific competition at early growth stages, but it increased rapidly after wheat and barley were harvested. Maximum cumulative N and P (but not K) uptake by intercropped maize were significantly higher than the uptake by monoculture maize, particularly when N fertilizer or film mulching was applied. Intercropping induced a significant temporal niche differentiation in maximum daily nutrient uptake rates (kg ha−1 day−1) between intercropped species. Fertilization had much stronger effects on maximum cumulative nutrient uptake of maize than that of wheat and barley. Mulching significantly increased the maximum cumulative nutrient uptake of maize and advanced the time to reach its maximum daily P and K uptake rates. Our study provides evidence of an important temporal niche differentiation mechanism (‘temporal complementarity’) in nutrient uptake rates between neighbouring plant species. A better understanding of temporal trajectories of interspecific nutrient uptake rates remains crucial if we want to maximize the nutrient‐use efficiency and sustain overyielding (i.e. high food production) in plant species‐diverse systems such as intercropping. Lay Summary